Building A Work Culture Through The Models of Improving The Quality of Human Resource - Herman Herman (IAIN Padangsidimpuan, 2021)
Human resource has a very strategic position and it is a prerequisite in building a work culture in an organization or institution. Building a work culture requires professional human resources with integrity, commitment, discipline and responsibility, and exemplary of good behavior. This research aims to describe the creation of a work culture through the models of improving the quality of human resource. The method of the study was a qualitative method with descriptive approach through library research by collecting and analyzing data from various literatures related to work culture and human resources. Based on the results of discussion, it shows that building a work culture should develop the quality of human resources through the various models of enhancing professionalism, integrity, discipline and responsibility, and good exemplary behavior of the employee. The results of this discussion could be a recommendation for all leaders of organizations or institutions and other stakeholders, so that improving the quality of human resources would be helpful for building a work culture